The Influence of the Problem-Based Learning Model Based on Song Media on Student Learning Outcomes in Science Learning in Class V Elementary Schools - Juliana Siregar, Santi; Janson Silaban, Patri; Dameria Simanjuntak, Sinta; Wulan Sari HS, Dyan; Juliana (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
Students who experience learning difficulties in natural science (science) lessons obtain unsatisfactory learning results and grades that do not fulfil the KKM. Quantitative research method is a research method based on positive philosophy which is used to examine research instruments and quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. In this research, researchers used experimental methods. The student's natural science (science) learning outcomes before being given treatment obtained an average score of 60.46. The normality test result is 0.150, so it can be concluded that the pre-test learning results are normally distributed. The student's natural science (science) learning outcomes after being given treatment obtained an average score of 82.46. The normality test result is 0.094, so it can be concluded that the post-test learning results are normally distributed. This can be proven with a correlation coefficient value of 0.960 which is a very strong interpenetration. The results of the T-test calculation to find out whether the hypothesis is accepted or rejected, the tcount 16,830 is greater than ttable 1,706, which means that there is an influence of Problem-Based Learning Based on Song Media on student learning outcomes. Thus, Ha is accepted and Ho is rejected.